Molecular recognition with soft biomaterials. Issue 4 (14th January 2020) - Clegg, John R.; Peppas, Nicholas A.
Abstract : This review and critique provides fundamental considerations and practical suggestions for fabricating new polymeric biosensors, drug delivery vehicles, and scaffolds for tissue regeneration with tunable molecular recognition properties. Abstract : Biomacromolecules and engineered materials can achieve molecular recognition if they engage their ligand with properly oriented and chemically complementary moieties. Recently, there has been significant interest in fabricating recognitive soft materials, which possess specific affinity for biological analytes. We present a summary and evaluation of current recognitive materials for biosensing, drug delivery, and regenerative medicine applications. We highlight the impact of material composition on the extent and specificity of ligand adsorption, citing new theoretical and empirical evidence. We conclude with a guide for synthesizing and characterizing novel recognitive materials, as well as recommendations for ligand selection and experimental design.